2014
DOI: 10.1007/s00125-014-3438-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of Wdr13 improves the metabolic phenotype of Lepr db/db mice by modulating AP1 and PPARγ target genes

Abstract: Aim/hypothesis Type 2 diabetes is a complex disease characterised by hyperglycaemia, hyperinsulinaemia, dyslipidaemia and insulin resistance accompanied by inflammation. Previously, we showed that mice lacking the Wdr13 gene had increased islet mass due to enhanced beta cell proliferation. We hypothesised that introgression of a Wdr13-null mutation, a beta cell-proliferative phenotype, into Lepr db/db mice, a beta cell-destructive phenotype, might rescue the diabetic phenotype of the latter. Methods Wdr13-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 38 publications
6
17
1
Order By: Relevance
“…Similarly, RAB3A is important for synaptic transmission, learning and memory (Yang et al, 2007). CAMK2A belongs to the CaM-kinase II family of proteins-known for their significant role in synaptic plasticity, long term potentiation (LTP), and learning and memory (Soderling, 1993). Levels of Vesicular glutamate transporter 1 (VGLUT1)—an important molecule for excitatory synapse and for maintaining LTP (Balschun et al, 2010) was also found to be increased in Wdr13 −/0 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, RAB3A is important for synaptic transmission, learning and memory (Yang et al, 2007). CAMK2A belongs to the CaM-kinase II family of proteins-known for their significant role in synaptic plasticity, long term potentiation (LTP), and learning and memory (Soderling, 1993). Levels of Vesicular glutamate transporter 1 (VGLUT1)—an important molecule for excitatory synapse and for maintaining LTP (Balschun et al, 2010) was also found to be increased in Wdr13 −/0 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular hyperproliferation due to downregulation of p21 in absence of WDR13, has also been reported [11]. We have also demonstrated that the introgression of Wdr13 -null mutation in obese and diabetic Lepr db/db mouse model resulted in reduction of serum free-fatty acids, liver triglyceride and systemic inflammation [12]. Cell proliferative phenotype in pancreas and amelioration of fatty liver, prompted us to study the response of Wdr13 -/0 mice to direct liver injury induced by chronic CCl 4 administration and regeneration therein.…”
Section: Introductionmentioning
confidence: 58%
“…Since our previous study [12] indicated amelioration of fatty liver phenotype upon deletion of Wdr13 in Lepr db/db mice, we analysed liver triglyceride levels in the present study. In contrast to our earlier study, we observed higher triglycerides level in the liver of CCl 4 administered Wdr13 -/0 mice as compared to that in CCl 4 treated wildtypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WDR13 was originally discovered by Singh on human X chromosomes Xp11.23 and is highly conserved in vertebrates, where it is prominently expressed in the brain, pancreas, ovary, and testis (Singh et al, ; Suresh et al, ). More recent studies have shown that mice lacking the Wdr13 gene develop mild obesity, hyperinsulinemia, and increased islet β cell proliferation (Singh et al, ; Singh et al, ; Singh et al, ), suggesting a potential role in diabetes. Moreover, we previously demonstrated a significant increase in WDR13 expression during differentiation of bovine myogenic satellite cells (MDSCs) (Tong et al, ).…”
Section: Introductionmentioning
confidence: 99%